Have you seen my potty? - Kelly, Mij.; McQuillan, Mary (Hauppauge, N.Y. : Barrons, 2007)
Poor little Suzy Sue has to find her potty before she can do something very important that she does every day.
School Library Journal
Kirkus Reviews
2-5.
P-K.